PENINGKATAN HASIL BELAJAR PPKN DAN KEAKTIFAN MURID MELALUI PENGGUNAAN MEDIA POHON LITERASI DI SEKOLAH DASAR - Annisa_Wulandari Nisa; Abdul Azis; Musdalifah Syahrir (LPPM Universitas Cipta Mandiri, 2024)
The aim of this research is to determine the improvement in PPKn learning outcomes through the useof literacy tree media for class V students at SDN Sudirman III, Makassar City. The research carriedout was classroom action research (PTK). This research was carried out in two cycles consisting ofplanning, implementation, observation and reflection which included four meetings. The subjects ofthis research were 21 students in class V at SDN Sudirman III, Makassar City, consisting of 11 boysand 10 girls. Data collection techniques are observation, tests (evaluation), and documentation. Thedata obtained was then analyzed using quantitative and qualitative descriptive analysis. The resultsachieved quantitatively are (1) Application of literacy tree media in student activity, responses andlearning outcomes for class V students at SDN Sudirman III Makassar City, namely an increase instudent activity and courage in each cycle, where student activity in cycle I is with an average value49.3 in the less active category increased in the second cycle to 88.1 in the very active category.Student responses in cycle I with an average of 66.1 in the response category increased in cycle II withan average of 80.9 in the very response category. (2) Improvement of PPKn learning outcomes and student learning activities in accordance with the results of observations during the classroom actionprocess. The average score obtained by students after taking the final test from cycle I to cycle II afterimplementing the learning model increased from 59.3 in cycle I to 87.9 in cycle II. The completion ofPPKn learning for class V students at SDN Sudirman III, Makassar City has also increased. In cycleI, from 9 (42.8%) students to cycle II, 18 (85.7%) students achieved learning completeness andclassical learning completion was achieved, namely 80%. The conclusion is that literacy trees canimprove PPKn learning outcomes and the activity of class V students at SDN Sudirman III,Makassar City.